Gynecologic Malignancies Post-LeFort Colpocleisis. (30th November 2014) - Elkattah, Rayan; Brooks, Alicia; Huffaker, R. Keith
Abstract : Introduction . LeFort colpocleisis (LFC) is a safe and effective obliterative surgical option for older women with advanced pelvic organ prolapse who no longer desire coital activity. A major disadvantage is the limited ability to evaluate for post-LFC gynecologic malignancies. Methods . We present the first case of endometrioid ovarian cancer diagnosed after LFC and review all reported gynecologic malignancies post-LFC in the English medical literature. Results . This is the second reported ovarian cancer post-LFC and the first of the endometrioid subtype. A total of nine other gynecologic malignancies post-LFC have been reported in the English medical literature. Conclusions . Gynecologic malignancies post-LFC are rare. We propose a simple 3-step strategy in evaluating post-LFC malignancies.